(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2014)
The present study was carried out to investigate the methanolic extract of leaf of Erioglossum rubiginosum and its fractionates (petroleum ether, carbontetrachloride and chloroform fractions) for their in vitro antioxidant, thrombolytic and cytotoxic activities. Among the different fractions, the carbontetrachloride soluble fraction (CTF) showed significant antioxidant activity (IC50=30.32±0.08 ?g/ml) as compared to standard ascorbic acid (IC50=5.87±0.21 ?g/ml) and BHT (IC50=27.50±0.64 ?g/ml). The extract also inhibited 58.44±0.97% lipid from peroxidation and reveled excellent phenolic profile of about 128.56±1.02 mg of GAE /g of extract. In the thrombolytic assay the highest % of clot lysis was exhibited by the chloroform soluble fraction (CF) (28.57±0.83%), while for streptokinase it was about 66.77±0.92%. The LC50 values were found within the range of 12.92 to 80.06 ?g/ml, while different solvent fractions were tested for cytotoxicity against brine shrimp nauplii. This is the first report of antioxidant, thrombolytic and cytotoxic activities of E. rubiginosum. Dhaka Univ. J. Pharm. Sci. 12(2): 153-158, 2013 (December) DOI: http://dx.doi.org/10.3329/dujps.v12i2.17612